2012
DOI: 10.1002/jcp.24096
|View full text |Cite
|
Sign up to set email alerts
|

Impact of testosterone on body fat composition

Abstract: An excessive food supply has resulted in an increasing prevalence of overweight and obesity, conditions accompanied by serious health problems. Several studies have confirmed the significant inverse correlation between testosterone and obesity. Indeed after decades of intense controversy, a consensus has emerged that androgens are important regulators of fat mass and distribution in mammals and that androgen status affects cellularity in vivo. The high correlation of testosterone levels with body composition a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
51
0
7

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(60 citation statements)
references
References 75 publications
2
51
0
7
Order By: Relevance
“…Perry et al found increases leptin levels in middle age women, followed by a decline in older women (Perry et al 1997). However, testosterone levels are inversely correlated with leptin concentration (De Maddalena et al 2012), and in aging males, testosterone level decrease (and is strongly related with the development of sarcopenia) (Maggio et al 2013). These results suggest a possible role for leptin in the physiological anorexia of aging in males, but not in females.…”
Section: Leptinmentioning
confidence: 99%
“…Perry et al found increases leptin levels in middle age women, followed by a decline in older women (Perry et al 1997). However, testosterone levels are inversely correlated with leptin concentration (De Maddalena et al 2012), and in aging males, testosterone level decrease (and is strongly related with the development of sarcopenia) (Maggio et al 2013). These results suggest a possible role for leptin in the physiological anorexia of aging in males, but not in females.…”
Section: Leptinmentioning
confidence: 99%
“…According to this, increased deposition of visceral adipose in hypogonadal subjects causes a further decrease in testosterone concentrations through conversion to estradiol by the enzyme aromatase. This leads to even more abdominal fat deposition and a greater degree of testosterone deficiency [39].…”
Section: Metabolic Syndrome and Testosterone Levels: The Role Of Medimentioning
confidence: 99%
“…The long-term effects causing central adiposity are observed in patients with Cushing's syndrome [45] and in patients treated with exogenous corticosteroid treatment [46] . Unlike their anabolic actions in muscle, androgens have catabolic functions in adipose tissue [47][48][49][50] . Low testosterone levels are associated with visceral obesity in men [47,48] , and AR knockout (KO) male mice exhibit obesity [49,50] .…”
Section: Lipid Metabolism In and Adipose Tissue And Livermentioning
confidence: 99%
“…Unlike their anabolic actions in muscle, androgens have catabolic functions in adipose tissue [47][48][49][50] . Low testosterone levels are associated with visceral obesity in men [47,48] , and AR knockout (KO) male mice exhibit obesity [49,50] . Moreover, testosterone treatment reverses the increase of body fat mass induced by glucocorticoids [9] .…”
Section: Lipid Metabolism In and Adipose Tissue And Livermentioning
confidence: 99%